Fontan Hemodynamics Investigation via Modeling and Experimental Characterization of Idealized Pediatric Total Cavopulmonary Connection - Andrey Porfiryev; Aleksandr Markov; Andrey Galyastov; Maxim Denisov; Olga Burdukova; Alexander Yu. Gerasimenko; Dmitry Telyshev (Applied Sciences, 2020)
Simulation of the human body normal operating conditions is the important issue in the engineering process of designing biomedical devices intended for implantation. As an example of such process the Fontan procedure aims to support the human body function. It is a standard palliative treatment method for patients with a functionally univentricular heart. Nevertheless, this procedure has significant drawbacks. For instance, overload of the only functional ventricle leads to the inevitability of the heart transplantation. Herein, we perform simulation and experimental characteristics of the pediatric total cavopulmonary connection (TCPC) influence on the blood flow. We investigate and design three different types of pediatric TCPC configurations; we detect fluorescent particles via a high-speed camera in order to analyze distribution of the blood flow velocity modulus in different types of TCPCs. Finally, we evaluate hydraulic power losses for various cases. This work is particularly relevant for the improvement of existing TCPCs quality that can extend the life of Fontan patients. Moreover, it also applies to the reduction of morbidity and mortality of the patients waiting for a heart transplantation.